Analisis Implikasi Kebijakan Penghapusan Dispensasi Perkawinan Anak di Bawah Umur terhadap Trauma Psikologis Jangka Panjang pada Generasi Muda di Kabupaten Majene - Abdul Samad; Ahmad Ahmad; Sudirman L; Syafaat Anugrah Pradana; Agus Muchsin; Aris Aris (AHKAM, 2025)
Child marriage remains prevalent in Indonesia despite the enactment of legal restrictions through Law No. 16 of 2019, with Majene Regency in West Sulawesi recording high case numbers driven by cultural, economic, and educational factors. This study aims to analyze the impact of the policy on the long-term psychological trauma of young people in Majene, focusing on mental rehabilitation and the formulation of local policy recommendations for victim recovery. A qualitative case study approach was employed, involving 25 participants aged 18–25 with a history of early marriage (70% female), selected using purposive and snowball sampling techniques. Data were collected through semi-structured interviews, community observations, and documentation, supported by the Trauma Symptom Checklist and descriptive statistical analysis using SPSS. Data were analyzed thematically following the Braun and Clarke approach. The findings reveal that although the policy reduced the number of cases from 193 in 2023 to 20 in 2025, the post-policy trauma rate increased, with 60% of participants exhibiting an average PTSD score of 2.8. Manifestations of trauma included chronic depression (72%), domestic violence (12 cases), suicidal ideation (10 cases), and a 1.98-fold higher risk of child stunting. Access to rehabilitation services remained low (40%), although support from the PKK (Family Welfare Movement) was found to reduce trauma intensity. These findings underscore the urgency of implementing culturally grounded trauma-informed care based on Mandar traditions and integrating holistic policies that combine peer counseling and economic support to break the cycle of intergenerational trauma and strengthen victim recovery at the local level.